Vibrational shifts of absorption bands of linear molecules diluted in high-density rare gases: Measurements and modeling for CO2-Rg and OCS-Rg. (May 2020) - Troitsyna, L.; Asfin, R.; Gennadiev, N.; Buldyreva, J.; Filippov, N.
Highlights: Measurements and calculations of IR band-origin shifts for CO2 /OCS-Rg. First spectral moment estimation by direct computation and by DID model. Band-shape transformation with increasing buffer-gas pressure. Abstract: Increase of buffer gas pressure causes redistribution of intensity in the IR absorption bands and, indicating the presence of vibrational perturbation, changes the first spectral moment value responsible for the band-origin position. Band-origin shift coefficients for the ν 3, 2 ν 3 and ν 2 bands of OCS and the ν 3 band of CO2 diluted in high-density Ar, Kr and Xe are measured and calculated by two methods: directly with available in the literature vibrationally dependent potential-energy surfaces for both initial and final vibrational states and assuming that vibrational dependence arises from the interaction of the permanent /transient dipole moment of the absorbing molecule and the dipole moment induced on the perturber. A comparative analysis of results is given, showing a general underestimation of calculations with respect to measurements.